2021
DOI: 10.1002/isd2.12181
|View full text |Cite
|
Sign up to set email alerts
|

Snags in mobile money in developing economies

Abstract: Lessening snags in the management of mobile money systems is a fundamental prerequisite. The study was motivated by the continuous mobile money management snags. Previous studies in developing economies focused mainly on technological algorithm for mobile money systems with untraceable attention given to management matters. The study aimed at lessening snags in the management of mobile money system. Underpinned by activity theory and guided by an interpretive paradigm, a qualitative inquiry was conducted. Semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This emphasizes the importance of providing technologies with the aim of benefiting the targeted population by meeting their requirements and needs. Digital inclusion reinforces the relevance, affordability, and sustainability of digital technologies, leading users to expand their skills and knowledge, and therefore empowering them within the Information Society (IS) (Pitula and Radhakrishnan, 2007;UN-Habitat, 2021;Kanobe et al, 2022).…”
Section: Digital Inclusion Of Vulnerable Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…This emphasizes the importance of providing technologies with the aim of benefiting the targeted population by meeting their requirements and needs. Digital inclusion reinforces the relevance, affordability, and sustainability of digital technologies, leading users to expand their skills and knowledge, and therefore empowering them within the Information Society (IS) (Pitula and Radhakrishnan, 2007;UN-Habitat, 2021;Kanobe et al, 2022).…”
Section: Digital Inclusion Of Vulnerable Groupsmentioning
confidence: 99%
“…Another phenomenon occurring simultaneously with the digital revolution is the aging of the population. Older people are particularly anxious about digital technologies and find it difficult to integrate them fully into the booming digital ecosystem (Kanobe et al, 2022;Mubarak and Suomi, 2022). For instance, studies have shown that up to 27% of the older urban population lacks Internet connectivity (UN-Habitat, 2021).…”
Section: Digital Inclusion Of Vulnerable Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, trust is added to TAM, making it more up to date and pertinent (Chircu & Kauffman, 2000). For the adoption of mobile banking, prior research has emphasized the significance of factors including self‐efficacy, security, privacy, ease of use, and social influence (SI) (Giovanis et al, 2019; Kanobe & Bwalya, 2022; Koksal, 2016; Tran & Corner, 2016; Zhang et al, 2018). Salimon et al (2021) have added cultural factors and gamification in TAM framework to study its impact on usage of smartphone banking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the second paper, Kanobe and Bwalya (2022) explore “Snags in Mobile Money in Developing Economies”. Their study was motivated by the continuous emergence of snags in the management of mobile money.…”
mentioning
confidence: 99%